(untitled) (Historia, 2021)
The Afrikaner and democracy II : the decades before 1948 In this second and last part of a series the authors show that one of the most intense Afrikaner debates of the thirties and forties revolved around the nature of liberal democracy, capitalism and imperialism. The need of so many poor Afrikaners, and the fact that capitalism was seen as the other side of the coin of British imperialism, brought about a situation where many Afrikaner thinkers and politicians sought refuge under the umbrella of national socialism. The main protagonist of this trend was the Ossewa-Brandwag (Ox-wagon Sentinel or OB), but in the power struggle with the National Party (NP), the last mentioned also became infected with national socialist about democracy. However, after the OB neutralised itself by not participating in the 1943 election, these ideas largely fizzled out. Nevertheless, in the process the NP started usurping the sovereignty which previously was reserved for the volk and parliament. In the end, this helped bring about a situation where the abuse of power of the NP reign became possible. In hierdie die tweede en laaste in 'n reeks artikels wys die skrywers daarop dat een van die mees intense Afrikanerdebatte van die dertiger- en veertigerjare oor die aard van liberale demokrasie, kapitalisme en imperialisme gewentel het. Die behoefte van soveel arm Afrikaners, en die feit dat kapitalisme gesien is as die anderkant van die imperialistiese munt, het 'n situasiese meegebring waarin baie Afrikaner denkers en politici by die nasionaal-sosialisme 'n toevlug gesoek het. Die hoofprotagonis was die Ossewa-Brandwag (OB), maar in die magstryd met die Nasionale Party (NP), het laasgenoemde ook gekontamineer geraak deur die idees van die nasionaal-sosialisme oor die demokrasie. Ná die OB dit self geneutraliseer het, deur nie aan die 1943-verkiesing deel te neem nie, het dié idees gekwyn. In dié tyd het die NP begin om die soewereiniteit wat voorheen vir die volk en die parlement beskore was, begin oorneem.